“Esto no es una mancia”: un análisis de las formas de diagnóstico y tratamiento en las medicinas alternativas = "This is not a mancia" : an analysis of the forms of diagnosis and treatment in alternative medicines - Bordes, Mariana (Ciencias sociales y religión, 2013)
The article aims to explore a series of dimensions related to the treatment offered from a particular alternative medicine: foot reflexology. In particular, the way in which the interpretative matrices around corporality end up outlining a diagnosis-treatment in which two opposing dimensions coexist is analyzed. First, a logic of objectivist aspirations that is forged in the recognition of a certain linearity between the actions of the therapist and the response of the body. Second, a multiple and relational logic that places us at the level of "body reasons", which refers to the existence of a non-controllable margin in therapy that neither the specialist nor the user can predict. The interest of this work lies in the understanding of the cosmovisional supports of alternative medicines and the margins that enable processes of transaction of senses with other symbolic, religious or medical systems.